Hands-On STEAM Programming: Microteaching with Micro:bit for Enhanced Learning - Margarita Rafti; Emmanouil D. Milakis; Constantina Corazon Argyrakou; Dimitra G. Vangeli; Maria Christina Katsarou (Journal of Hypermedia & Technology-Enhanced Learning, 2025)
This study explores the application of microteaching as an effective pedagogical strategy for teaching sequencing structures in programming through STEAM (Science, Technology, Engineering, Arts, and Mathematics) activities. Leveraging the Micro:bit platform, the research integrates hands-on learning with transdisciplinary problem-solving to enhance conceptual understanding among elementary students. The study involved a structured action research methodology, engaging two sixth-grade students in constructing and programming a Christmas tree model using LEDs and the Micro:bit environment. The findings highlight the significant role of microteaching in fostering engagement and comprehension, as students transitioned from foundational programming knowledge in Scratch to more advanced applications involving hardware. Despite challenges such as time constraints and difficulties in knowledge transfer, the approach demonstrated measurable improvements in students’ understanding of sequencing. These results underscore the potential of combining microteaching and STEAM methodologies to make abstract programming concepts accessible, engaging, and practical for young learners. Recommendations for future implementations include enhanced scaffolding, iterative learning opportunities, and extended session durations to address identified challenges and optimize outcomes.